Testing the Effectiveness of Using Song Lyrics on Poetry Writing Skills: an Experiment at MAN 1 Karanganyar - Hanifah, Shofi; Suhita, Raheni; Rakhmawati, Ani (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
The lack of student’s poetry skills needs to be improved by utilizing song lyrics to inspire students in writing poetry. The purpose of this research was to determine whether there is an effect of song lyric on student’s poetry skills. This research used a pretest-posttest control grup design with sampling used purposive sampling with 37 students in the experimental group dan 34 students in the control group. The independent variable in this research song lyric, while the dependent variable is poetry writing skill. The prerequisite test conducted used content validity teat, tes-retes reliability test, liliefors normality test, and barelett homogeneity test.  Hypothesis testing in this research used one-way ancova test. The result hypothesis testing found a significance value < the significance level, namely 0,006<0,05. So the results showed that there was an effect of using the song lyric on poetry writing skills  of high school students. The Cohan’s effect size test was carried out by obtaining a result of 0,69 which shows that the effect of this research is in the medium category.